A hybrid setup for rodent hyperpolarized metabolic imaging using a clinical magnetic resonance scanner - Ditte Bentsen Christensen; Ingeborg Sæten Skre; Jan Henrik Ardenkjær-Larsen; Mor Mishkovsky; Mathilde H Lerche (Journal of Magnetic Resonance Open)
Metabolic magnetic resonance spectroscopic imaging using hyperpolarized contrast agents offers a non-invasive approach to monitoring real-time in vivo energy metabolism. The technique involves hyperpolarizing a contrast agent in a polarizer, administering it to a living system, and then imaging its distribution and metabolites using a magnetic resonance scanner. Over the past two decades, the method has transitioned from in vitro studies to clinical research, with an increasing focus on clinical applications.Here, we present a hybrid system that adapts a clinical magnetic resonance scanner for pre-clinical rodent experiments. The hybrid system includes (1) a customizable, 3D-printable animal cradle setup and (2) optimized imaging strategies, including coil configurations, metabolic contrast agent administration, and proton imaging acquisition. The system enables 13C dynamic imaging, which we illustrate with detection of hyperpolarized [1–13C]pyruvate and its metabolites in the mouse brain. We detail the experimental procedure, provide practical guidance, and showcase the capabilities of the system with example data from mouse brain imaging.This hybrid setup bridges the gap between clinical and pre-clinical research, enabling iterative testing of equipment, imaging sequences, and hypotheses across phantoms, in vivo rodent models and clinical settings. By facilitating a smoother translation, both forward and reverse, between pre-clinical and clinical applications, this approach enhances the potential for advancing metabolic imaging research.